SKP (Sasaran Kerja Pegawai) dan Implikasinya pada Kinerja PNS di Lingkungan SMP Negeri 1 Meral Kabupaten Karimun - Ferawati, Said Nuwrun T (Prodi Ilmu Administrasi Negara, 2019)
The research is descriptive research that is both explorative, to express a thing exists. The population was an appraiser (2 persons), a superior an appraiser (3 persons), and civil servants (28 people). Sample rates of return performed on all employees in units of the organization. The data collection was done by using quesioner covering knowledge assessors, substance, method , time , assessors mechanism and obstacles. The results of the analysis shows knowledge assessors about those policies related with the work performance civil servants is enough, but not applied in accordance with the provisions and have not been able to provide an assessment objectively. A method of assessment evaluation has been good enough working with the target of being measurable and clear but there are still some judgment behavior civil servants that were not clear indicators and the measurement based on the principles of approximately. Found some psychological so assessors could not make an assessment performance fair, in the form of assessment work performance that objective. The results of target work employees not yet used for the establishment of civil servants, and used only for promotion just requirements.